Study of impact of biological additives on cryoprotective action of multicomponent media based on combinations of glycerol and polyvinyl alcohol when freezing human erythrocytes - Hvozdiuk, Yana; Kompaniets, Antonina (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):310